Muludan Acculturation in Javanese Areas in Enhancing The Understanding of Islamic Values - Zahara, Aulia Jihan (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research focuses on the process of Muludan cultural acculturation in Java and how it contributes to people's understanding of Islamic values. Islam entered Indonesia by incorporating itself into existing cultural traditions without erasing them, resulting in a unique interaction between the two. The Muludan tradition, celebrated annually in different ways in each region, is a prime example of this cultural acculturation. The research utilizes an ethnographic approach to study how Muludan culture is implemented in Java and how it enhances people's understanding of Islamic values. The findings highlight that Muludan culture successfully combines tradition with Islamic principles, teaching individuals about values such as gratitude, tolerance, and cooperation. The practice of Muludan contributes to the internalization of these values and is an effective means of increasing understanding of Islamic values, while also preserving local culture and maintaining harmony.Keywords: Acculturation, Muludan, Javanese, Islamic Values